(untitled) (International Journal of Engineering and Computer Science, 2017)
Software Defined Networking (SDN) is an emerging architecture in the field of networking in which the control plane and forwarding plane of traditional networking devices (e.g. Switches, Routers) are decoupled. The network-wide traffic flow can be directly programmed. SDN plays an important role in today’s enterprises and applications with drastically changing requirements which are monitored and adapted by the change in traffic flows through the networking devices. This survey paper on SDN provides an outline on the standard communication interface, characteristics of SDN and the pros and cons that are associated with SDN architecture.